2021
DOI: 10.3389/frvir.2021.740795
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Immersion: Implementing Personalized Components Into Virtual Reality for Veterans With Post-Traumatic Stress Disorder

Abstract: With the application of virtual reality (VR), tailored interventions can be created that mirror the traumatic experiences of veterans with post-traumatic stress disorder (PTSD). Visual elements can be mimicked, and auditory and other senses stimulated. In doing so, the degree of immersion can be adjusted to optimize the therapeutic process. Objectively measuring the sensory immersion is key to keep subjects within their personal window of tolerance. Based on this information the therapist can decide manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…As with most VR enhanced therapies, the content of the VR scenarios was similar to the narrative of the patients but does not correspond exactly. Although it has been suggested that individualized VR scenarios are important (see (Van Veelen et al, 2021), both very realistic although generic scenarios (Skip et al, 2010) as well as abstract scenarios (Botella et al, 2015) have been found to be effective and at the theory underlying exposure based treatment for PTSD places importance on the ability of the patient to emotionally process the traumatic memory (Foa and Kozak, 1986) and employs techniques to enhance this, for instance asking the patient to retell the narrative using first person, present tense. Since this process can be challenging for patients, methods to enhance prolonged exposure have been examined (e.g., (Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with most VR enhanced therapies, the content of the VR scenarios was similar to the narrative of the patients but does not correspond exactly. Although it has been suggested that individualized VR scenarios are important (see (Van Veelen et al, 2021), both very realistic although generic scenarios (Skip et al, 2010) as well as abstract scenarios (Botella et al, 2015) have been found to be effective and at the theory underlying exposure based treatment for PTSD places importance on the ability of the patient to emotionally process the traumatic memory (Foa and Kozak, 1986) and employs techniques to enhance this, for instance asking the patient to retell the narrative using first person, present tense. Since this process can be challenging for patients, methods to enhance prolonged exposure have been examined (e.g., (Flanagan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that adding odors that are related to the traumatic event will improve treatment outcomes, and this has been carried out both in hypnotherapy (Abramowitz and Lichtenberg, 2010) as well as in the context of Virtual Reality enhanced Exposure Therapy (Van Veelen et al, 2021;Lo and Hurley, 2022), This case study describes the treatment of combat related PTSD using VR enhanced exposure therapy with the addition of olfaction.…”
Section: Introductionmentioning
confidence: 99%